1994
DOI: 10.1111/j.1349-7006.1994.tb02074.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Childhood Cancer in Osaka, Japan, 1971–1988: Reclassification of Registered Cases by Birch's Scheme Using Information on Clinical Diagnosis, Histology and Primary Site

Abstract: In 1971–1988, 4,021 malignant tumors occurring among children under 15 years of age were registered in the Osaka Cancer Registry, a population‐based registry which covers Osaka Prefecture, Japan. These patients were reclassified into 12 diagnostic groups by Birch's scheme using information on clinical diagnosis, histology and primary site. The annual age‐standardized incidence rate for childhood cancer per million children was 130.3 for males and 104.9 for females in 1971–88. Comparing the incidence rates for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…The decrease in Osaka may have been partly due to changes in the diagnosis or classification of ALL and ANLL, although the authors were of the opinion that most of the leukaemia changes they observed were real (Ajiki et al, 1994 (Coebergh et al, 1989). In north-west England 1954-88, there was no significant trend in the incidence of childhood ANLL (Blair and Birch, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in Osaka may have been partly due to changes in the diagnosis or classification of ALL and ANLL, although the authors were of the opinion that most of the leukaemia changes they observed were real (Ajiki et al, 1994 (Coebergh et al, 1989). In north-west England 1954-88, there was no significant trend in the incidence of childhood ANLL (Blair and Birch, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these tumours are osteosarcoma or Ewing sarcoma (Stiller et al, 2006a), in the United Kingdom 54% being osteosarcoma, 39% Ewing sarcoma, 2% chondrosarcoma and 5% other types (Stiller, 2007). Worldwide, trends in incidence rates for childhood bone tumours have remained constant (McNally et al, 2001;Stiller et al, 2006a;Magnanti et al, 2008), although a few studies have reported increases (Ajiki et al, 1994;Gurney et al, 1996). The substantial improvement in survival over the past 40 years (Arndt et al, 2007) has been attributed to chemotherapy (Stiller et al, 2006a).…”
mentioning
confidence: 99%
“…[28] This is consistent with the findings in this study. There is a male predominance in the cases of lymphoma as a whole and also in the cases of Burkitt's lymphoma which is the general pattern in studies in other parts of the country and the world [2,3,7,9,[29][30][31][32][33][34][35][36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to the findings in Jos, [15] Sokoto [19] and Lagos. [2] In Europe, however, Burkitt's lymphoma appears in older children [34][35][36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation